Calves with Arthritis - Changes in Antioxidant Parameters - Yakan, Selvinaz (Acta Scientiae Veterinariae, 2023)
Background: In a healthy organism, oxidants and antioxidants are in balance. However, in cases such as inflammation, infection, and stress, this balance is disrupted in favor of oxidants, creating oxidative stress that can cause damage to cells or tissues. It is known that oxidative stress plays a role in the pathogenesis of many diseases. Determination of oxidant and antioxidant balance, especially in inflammatory diseases, plays an important role in elucidating the pathogenesis of the disease and developing treatment strategies. This study, it was aimed to reveal the oxidant status in inflammatory disease of calves with septic and aseptic arthritis. Materials, Methods & Results: The material of the study consisted of 21 calves up to 2 months old, of different races and genders, 14 (9 male, 5 female) with arthritis and 7 healthy (control, 5 male, 2 female). Of the calves with arthritis, 11 were septic and 3 were acute aseptic. In the calves with arthritis, the affected joint or joints were determined by clinical examinations. By palpating the joints, swelling, local temperature increase, tension in the joint capsule, presence of pain, and the presence and severity of lameness were examined. The color, clarity, viscosity, odor, and clot formation of the synovial fluid were examined and determined to be septic or aseptic. To determine the antioxidant status, the levels of malondialdehyde (MDA), which is the most important oxidative stress marker, and superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), which are the enzymatic antioxidant enzymes, were measured spectrophotometrically in serum samples. Vitamin E, C, and A levels, which are nonenzymatic antioxidants, were also measured colorimetrically. In the clinical examination, lameness was detected in the relevant extremity of all patients with arthritis. In the macroscopic examination of the synovial fluids taken from animals with arthritis, the colors of the synovial fluids varied between yellow and yellow tones in 11 cases; in 3 cases, it was determined that they were red and brown. It was observed that the colors of the synovial fluids were transparent in the subjects in the control group. It was observed that the synovial fluid clarity of the calves with arthritis was lost, with severe turbidity (+++) in 3 cases, moderately turbid (++) in 6 cases, slightly turbid (+) in 2 cases, and clear (-) in 3 cases. It was observed that the viscosity of synovial fluid taken from calves with arthritis decreased in varying degrees according to the severity of the disease, severe (+++) in 5 cases, moderately decreased (++) in 4 cases, slightly decreased (+) in 2 cases, and normal in 3 cases. It was determined that the viscosity of the synovial fluid taken from the calves in the control group was normal. There was a statistically significant difference between the groups in terms of MDA (P < 0.01), SOD (P < 0.01), GSH-Px (P < 0.05), vitamin E (P < 0.001), and vitamin C (P < 0.01), while MDA levels increased in calves with arthritis, SOD and GSH-Px activities and vitamin E and C levels decreased significantly. Although there was no statistically significant difference in CAT (P > 0.05) enzyme activity, it was determined that it was at a lower level in calves with arthritis, and there was no significant difference between the groups in terms of vitamin A (P > 0.05). Discussion: According to the results of the study, there is an increase in oxidative stress and a decrease in antioxidant status in calves with arthritis. It is thought that these changes may be due to efforts to reduce tissue damage by reducing lipid peroxidation. As a result, it was determined that oxidant and antioxidant balance was impaired in calves with arthritis, and oxidative stress and lipid peroxidation developed due to the increase in free radicals. It is thought that giving additional antioxidants to the calves may contribute to the recovery of the disease and reduce treatment costs. Keywords: arthritis, antioxidant, calve.